(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
This article is about teaching English to multilevel classes, and gives information about challenges, benefits, opinions how to conduct multilevel classes.A multi-level classroom is one in which some pupils are conversant with the Roman alphabet and others are not. Finally, the phrase multi-level can apply to a group of students who work together and have a wide range of abilities.